تأثير بيئة العمل على الرضا الوظيفي للأكاديميين: دراسة حالة الجامعات الخاصة في المملكة العربية السعودية - أبو شعيشع، أحمد عبدالحميد محمد (جامعة سوهاج - كلية التجارة, 2020)
كان الغرض الرئيسي من هذه الدراسة هو فحص العلاقة بين بيئة العمل والرضا الوظيفي للأكاديميين في الجامعات الخاصة في المملكة العربية السعودية. والعوامل التي تؤثر في بيئة العمل هي حرية الأكاديميين، وإشراك أصحاب المهن، وسياسات الإدارة، وعلاقات زملاء العمل وصاحب العمل وعلاقات الموظفين والتي تم‏ استخدامها كمتغيرات مستقلة أما الرضا الوظيفي للأكاديميين فقد استخدم كمتغير تابع. تم استخدام الاستبيان ب 5 نقاط على مقياس LIKERT لجمع بيانات من 105 أكاديمي في الجامعات الخاصة في المملكة. تم تحليل البيانات من خلال SPSS 22‏ باستخدام أدوات إحصائية مثل الإحصاء الوصفي، ارتباط بيرسون والانحدار الخطي البسيط. النتائج تشير إلى أن هناك علاقة إيجابية بين جميع عوامل بيئة العمل والرضا الوظيفي لدى الأكاديميين. كما وجدت الأبحاث أن علاقات صاحب العمل-الموظف هي أهم عامل لبيئة العمل في جامعات الأعمال الخاصة في باكستان. وعليه اقترح أن إدارة الجامعات ينبغي أن تركز على بيئة عمل إيجابية وخاصة عامل العلاقة بين صاحب العمل والموظف لزيادة الرضا الوظيفي بين الأكاديميين، والذي قد يؤدي إلى أداء أعلى. نظرا لأن البحث الذي تم إجراؤه فقط على أكاديميين في الجامعات الخاصة في المملكة، لا يمكن تعميمه على جميع قطاعات البلد. يجب زيادة المتغيرات وحجم العينة في البحوث المستقبلية للحصول على نتائج أفضل.
The main purpose of this study was to examine the relationship between the work environment and job satisfaction for academics in private universities in the Kingdom of Saudi Arabia. The factors that affect the work environment are the: freedom of academics, the involvement of professionals, management policies, co-workers and employer relations and employee relations that have been used as independent variables. The job satisfaction of academics has been used as a dependent variable. The 5- point questionnaire on the likert scale was used to collect data from 105 academics at private universities in the Kingdom. Data were analyzed by SPSS 22 using statistical tools such as descriptive statistics, Pearson correlation and simple linear regression. The results indicate that there is a positive relationship between all factors of the work environment and job satisfaction among academics. Research has also found that: employer- employee relationships are the most important factor for the work environment in private business universities in Pakistan. Accordingly, he suggested that university administration should focus on a positive work environment, especially the relationship factor between the employer and employee to increase job satisfaction among academics, which may lead to higher performance. Since the research conducted only for academics in private universities in the Kingdom, it cannot be generalized to all sectors of the country. Variables and sample size should be increased in future research to obtain better results.
Keywords: التعليم العالي -- الرضا الوظيفي -- هيئة التدريس -- الجامعات الخاصة -- السعودية